FAKTOR PENGARUH TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Dame Ria Rananta Saragi (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
The research is to determine the effect of Sales Growth, Liquidity and Leverage on Profitability partially and simultaneously. The population in this study was 30 food and beverage sub-sector companies with a sampling technique based on criteria using purposive sampling. The samples obtained were based on the criteria of 30 food and beverage sub-sector companies. This type of research is quantitative with a causal associative approach. The data analysis technique used is quantitative with descriptive statistics using SPSS. Sales Growth partially has a positive and significant effect on Profitability, Liquidity has a partial positive and significant effect on Profitability, Leverage partially has a negative and significant effect on Profitability, and Sales Growth, Liquidity and Leverage simultaneously have a positive and significant effect on Profitability.